PENANAMAN BUDAYA ANTIKORUPTIF DI KAMPUS MELALUI PENDIDIKAN ANTIKORUPSI - Luh Puji Astiti (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
Efforts to eliminate corruption in Indonesia require treatment that goes beyond mere prosecution by law enforcers. Efforts to tackle and deal with corruption must be accompanied by a determination to stop it at its roots so that it cannot regenerate anymore, and this can be achieved through education. Students as educated human beings become a driving force from an intellectual point of view, they must become agents of change. In order to be able to be active in their role in stopping this culture of corruption, students need debriefing, namely sufficient insight to know the insides of corruption and how to stop it. Anti-corruption education actually needs to demonstrate techniques to students so that students are able to clearly understand the problems of corruption that occur. This article explains anti-corruption education and to understand how this education is given to students as an effort to eradicate corruption. Efforts to provide insight can be through various ways, namely socialization, campaigns, seminars, and lectures. Anti-corruption education aims to transfer knowledge about Pancasila values that are not pro against corrupt culture. The goal of sustainability of this anti-corruption education is to foster a community spirit that is far from corrupt actions so that it encourages national development which starts here with education for students as the successors of the nearest nation who are able to continue the baton of the next nation's leadership which is far from a culture of corruption.